Penerapan Standard Recipe Makanan di Kicthen Hotel Grand Q Gorontalo - Tri Rachmad Irianto; Asminar Mokodongan; Yumanraya Noho; Lisna Bantulu (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
This research aims to determine the application of standard food recipes in the Grand Q Gorontalo hotel kitchen. This research uses descriptive qualitative research, data collection procedures obtained through collecting observations, interviews, documentation and literature study, data sources obtained from primary and secondary data. Based on the research results, it can be concluded that standard recipes have a very important role, with standard recipes it can make it easier for every cook to process food products with the same quality and consistency of food, (starting from portions, ingredients, sizes, cooking methods, and the cooking time is completely stated according to what is needed)